Analisis Cluttering (Gangguan Irama Bicara) pada Remaja Usia 20 Tahun - Oktaviansyah, Farizal; Putra, Dona Aji Karunia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the forms and factors that cause speech rhythm disorders experienced by adolescents aged 20 years. This research uses descriptive qualitative method.Data collection was carried out using a test, simak and catat. The results showed that, on the reading test, Hl had a "fast" rhythm disorder with "unclear" articulation and a phonological disorder in the form of phoneme substitution.In the interview, Hl's speaking rhythm was still classified as "fast" and his articulation was also "less clear" so that a syntactic disorder emerged in the form of difficulty in arranging word order correctly.The factors that cause Hl to experience speech rhythm disturbances are the lack of frequency of speaking and communicating.Internal or psychological factors that make it difficult for Hl to speak are insecurity or nervousness that makes him rush in finishing his speech.